2021
DOI: 10.1016/j.amepre.2021.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Prison Therapeutic Diversion Unit on Mental and Behavioral Health Outcomes

Abstract: Introduction: Incarcerated individuals with mental health disorders are disproportionally sent to restrictive housing (i.e., solitary confinement), which is known to have deleterious impacts on mental health. In response, North Carolina's prison system developed Therapeutic Diversion Units, treatment-oriented units for incarcerated individuals with high mental health needs who cycle in and out of restrictive housing. This analysis compares the impact of restrictive housing and Therapeutic Diversion Units on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Inpatient mental health admissions represent a severe mental healthrelated outcome. We previously found that current enrollment in TDUs was associated with a protective effect on inpatient mental health admissions, as compared to restrictive housing (Remch et al, 2021). However, findings from the current analyses indicate that following release from these environments, the hazard of inpatient mental health admissions was potentially elevated post-TDU compared to postrestrictive housing.…”
Section: Tablecontrasting
confidence: 65%
See 3 more Smart Citations
“…Inpatient mental health admissions represent a severe mental healthrelated outcome. We previously found that current enrollment in TDUs was associated with a protective effect on inpatient mental health admissions, as compared to restrictive housing (Remch et al, 2021). However, findings from the current analyses indicate that following release from these environments, the hazard of inpatient mental health admissions was potentially elevated post-TDU compared to postrestrictive housing.…”
Section: Tablecontrasting
confidence: 65%
“…In prior analyses, we found that TDU enrollees demonstrated a considerably reduced rate of self-injury while enrolled in the program, as compared to their peers in restrictive housing (Remch et al, 2021). In this analysis, we found an increased rate of self-injury post-TDU compared to post-restrictive housing.…”
Section: Tablesupporting
confidence: 47%
See 2 more Smart Citations
“…Men who met these criteria at the time of RDU enrollment contributed 417,343 person-days to the RDU-exposed group. Men who met these criteria while placed in RHCP, and who had not been previously enrolled in RDU or another restrictive housing diversion program (i.e., Therapeutic Diversion Units (TDUs, which have also previously been evaluated)) (Remch et al 2021 , 2022 ), contributed 480,479 person-days to the RHCP-exposed group. Men who contributed person-days to the RHCP-exposed group and later enrolled in the RDU could contribute person-time to both groups.…”
Section: Methodsmentioning
confidence: 99%